Robotics in Total Knee Arthroplasty (2019)
Total knee arthroplasty (TKA) is a highly successful operation that improves patients' quality of life and functionality. Yet, up to 20% of TKA patients remain unsatisfied with their clinical result. Robotic TKA has gained increased attention and popularity as a means of improving patient satisfaction. The promise of robotic-assisted TKA is that it provides a surgeon with a tool that accurately executes bone cuts according to presurgical planning, as well as provides the surgeon with intraoperative feedback helpful for restoring knee kinematics and soft tissue balance. Several systems are now available, each with their own advantages and disadvantages. Evidence that the use of robotics will lead to improved implant survival, function, and patient-reported outcomes is slowly being accumulated, but this has not been clearly proven to date. Recent literature does show that the use of robotics during TKA is not associated with increased surgical time or complications. The goal of this review is to provide an objective assessment of the evidence surrounding robotic technology for TKA. © 2019 2019 by Thieme Medical Publishers, Inc. All rights reserved.